A208 PREDICTORS OF OUTCOMES IN PSC: RETROSPECTIVE ANALYSIS OF TWO TERTIARY CARE CENTERS IN BC. (4th March 2021) - Chahal, D; Bedi, H K; Marquez, V; Yoshida, E M; Ko, H; Salh, B
Abstract: Background: Primary sclerosing cholangitis (PSC) is a chronic inflammatory disorder of the bile ducts. PSC can rapidly progress to cholangiocarcinoma and death. Many clinical features of PSC, as well as its relationship with diseases such as IBD, remain ill-defined. These features are important for disease modeling and clinical trial design. Aims: To identify features of PSC that may aid in disease modeling and outcomes prediction. Methods: Patients with a diagnosis of PSC with visits between 2012 and 2018 were identified and data were extracted. Survival analysis was performed, with time defined as time of PSC diagnosis to time at clinical endpoint. The clinical endpoint for survival analysis was defined as development of cholangiocarcinoma, liver transplantation or death. Univariate and multivariate Cox-regression was then performed. Results: 169 patients (99 male, 70 female) were identified. Of these, 102 (60.4%) had a diagnosis of IBD (84 UC). 138 were Caucasian, 9 East Asian, 9 South Asian and 13 Middle East. Mean age at PSC diagnosis was 39.3, IBD diagnosis 29.3 years. Mean time to next diagnosis in those with PSC-IBD was 7.7 years. Of those with PSC-IBD, IBD preceded the diagnosis of PSC in 69 (67.6%) patients. 22 (13.0%) had concurrent liver disease, including 14 AIH and 1 PBC overlap. In those with UC, disease was most often pancolitis (57.8%), with noticeable rate of backwash ileitis (23.3%). There were 26 patients with current or prior use of Infliximab, 14 with Humira, and 6 with Vedolizumab. 28 (16.6%) patients had a partial or total colectomy. 35 (20.7%) patients had diagnoses of cancer, including 16 cholangiocarcinoma, 2 gall bladder carcinoma, and 4 colorectal. 33 (19.5%) patients received liver transplant, and 31 (18.3%) died. Most frequent cause of death was cholangiocarcinoma (12, 38.7%). Univariate analysis identified increased age at PSC diagnosis, presence of IBD, increased age at IBD diagnosis, diagnosis of IBD prior to PSC, increased time from diagnosis of IBD to PSC, diagnosis of UC as opposed to Crohn's, and lack of Infliximab use as significant predictors of our clinical endpoints (p<0.05). Multivariate analysis only identified increased age at PSC diagnosis, presence of IBD, and diagnosis of IBD prior to PSC as predictors. Conclusions: PSC affects persons of various ethnic backgrounds. Diagnosis of IBD appears to precede PSC in most PSC-IBD cases, and the temporal relationship may impact outcomes, possibly due to delayed diagnosis of PSC. UC has a worse disease course than Crohn's. Cholangiocarcinoma still accounts for a large burden of overall death in PSC, and strategies for early diagnosis should be explored. More studies are required to delineate the relationship between biologic use and PSC outcomes. The major limitation of our study is the smaller sample size that may have limited statistical power. Funding Agencies: NoneNone